Role of hydration and micellar shielding in tuning the structure of single crystalline iron oxide nanoparticles for designer applications. Issue 12 (12th May 2021) - Arbi, Ramis; Ibrahim, Amr; Goldring‐Vandergeest, Liora; Liang, Kunyu; Hanta, Greg; Hui, Lok Shu; Turak, Ayse
Abstract: Different physicochemical properties of nanoscale iron oxides have been useful in enabling various applications. Desirable biochemical, magnetic, and catalytic properties result from the structure and size of the iron oxide polymorph particles. To produce monodispersed single crystalline particles, PS‐ b ‐P2VP reverse micelle templating has proven to be a convenient low temperature method. Here, Raman spectroscopy and quantitative nanomechanical mapping analysis are used to provide a full picture of the formation and transformation processes that occur within the reverse micelle templates. Surprisingly, shielding of the hygroscopic FeCl 3 precursor salt against hydration rather than complexation with the pyridine is responsible for the formation of γ ‐Fe 2 O 3 particles. Additionally, micelle shielded nanoparticles not only exhibited a uniform size distribution and ordered dispersion, but also an increased transition temperature for the γ to α ‐phase transition, up to 700 ∘ C, making them much more stable than traditional nanoparticles. Using these key understandings of particle formation, nanoparticles can be tuned with composition ranging from a purely spinel ( γ ‐Fe 2 O 3, Fe 3 O 4 ) to a purely hexagonal phase ( α ‐Fe 2 O 3 ), and varying ratios of the three phases, while maintaining a fixed particle size. Modifying parameters offer intriguing opportunities to tailor designer iron oxide nanoparticles for targeted applications with a facile and scalable technique. Abstract : Tunable crystal structure for single crystalline iron oxide nanoparticles taking advantage of diblock copolymer reverse micelle template properties